Evaluating Recidivism Among Drug Offenders in Florida's Residential and Non-Residential Substance Abuse Treatment Programs, 1991-1997 - Linster, Richard L. ([Verlag nicht ermittelbar], 2002)
This study was undertaken to investigate the relationship, if any, between drug treatment and success or failure of drug-involved offenders on probation/community supervision. Further, the researchers sought to evaluate the outcomes of drug-involved offenders admitted to (1) secure residential substance abuse treatment (RSAT) programs, (2) non-secure residential drug treatment programs, (3) non-residential drug treatment programs, and (4) no drug treatment programs. Data were collected from administrative records provided by the Florida Department of Corrections, specifically case history records of offenders admitted to supervision in the community from July 1, 1991, through June 30, 1997. Part 1 is comprised of all cases admitted to community supervision between July 1, 1991, and June 30, 1993 (fiscal years 1991 and 1992) and treated in a secure residential drug treatment program. Part 2 is comprised of all cases admitted to community supervision from July 1, 1991, through June 30, 1995, receiving treatment in a non-secure residential drug treatment program. Part 3 contains data on offenders admitted to non-residential drug treatment programs, whose community supervision admissions were between July 1, 1991, and June 30, 1993. Part 4 contains data on offenders admitted to non-residential drug treatment programs, whose community supervision admissions were between July 1, 1993, and June 30, 1995 (fiscal years 1993 and 1994). Part 5 contains data on cases admitted to community supervision between July 1, 1991, and June 30, 1993, who did not receive drug treatment of any kind. Cases admitted to community supervision between July 1, 1993, and June 20, 1995, receiving no drug treatment are contained in Part 6. Each supervision admission record contains a history of subsequent court actions that were complete through December 31, 1997. Variables for all parts include population estimates, unemployment rates, population by age-specific categories, violent and nonviolent index offenses, per capita personal income, clearance rates, split sentence flag, primary offense disposition, primary offense felony level, current commitment years supervised, supervision type, whether current offense included a drug charge, number of prior supervision terms, number of prior commitments, reasons for failure, treatment facility code, number of drug sale/traffic offenses, outcome of supervision period, and reasons for prison intake. Demographic variables include race and gender.